Domino Twofold Heck/6π-Electrocyclization Reactions of 1,2-Dihaloalkenes - Hussain, Munawar; Sung, Tran Van; Langer, Peter (Synlett, 2012)
Domino twofold Heck/6π-electrocyclization reactions of 1,2-dihaloalkenes allow for a convenient synthesis of benzene derivatives. In recent years, this strategy has been applied to various 1,2-dihalogenated carbocyclic alkenes and heterocycles, and a variety of benzo-fused ring systems have been prepared. The electrocyclization reactions proceed well for five-membered, but not for six-membered heterocycles.1 Introduction2 Carbocyclic Substrates3 Heterocyclic Substrates3.1 Thiophenes3.2 Pyrroles3.3 Imidazoles3.4 Furans3.5 Benzothiophenes3.6 Indoles3.7 Benzofurans3.8 Pyridines3.9 Pyrazines3.10 Quinoxalines4 Conclusions
Keywords: electrocyclization reactions; domino reactions; Heck reaction; palladium; heterocycles